Dead Sea pollen record and history of human activity in the Judean Highlands (Israel) from the Intermediate Bronze into the Iron Ages (∼2500–500 BCE) - Langgut, Dafna (Palynology, 2014)
A detailed pollen record for the time interval of ∼2500–500 BCE, which covers the time period of the Intermediate Bronze Age (Early Bronze Age IV) into the Iron Ages in the Levant, is presented. The study was conducted in the Ze'elim Gully, which drains the southern Judean Highlands into the Dead Sea. During the Bronze and Iron Ages, the Judean Highlands exhibited dramatic settlement fluctuations. To better understand these oscillations, high-resolution fossil pollen data were combined with a recent pollen data set, lithological features, radiocarbon dating and palaeohydrological information derived from the Dead Sea levels. Due to the occurrence of hiatuses in this fluvial environment, we used a composite profile which was based on two palynological-sedimentological profiles. This integrated information enabled us to reconstruct in great detail for the first time the environmental conditions in relation to the picture derived from archaeological field-work in the Judean Highlands. Evidence for drier climate conditions at the end of the Late Bronze Age may account for the dramatic changes in the settlement pattern which include the destruction of a large number of urban centres and shrinkage of other major sites, not only in the Judean Highlands but in the entire southern Levant. This arid phase may have been one of the reasons for the collapse of eastern Mediterranean civilizations in the mid-thirteenth and twelfth centuries BCE. The improved conditions in the Judean highlands during the Iron Age I (evident by the increasing percentages of both Mediterranean elements and agricultural taxa, e.g. olive and cereals) enabled the recovery of settlement activity, which is the backdrop for the rise of ancient Israel.